City’s Master Plan of Belém (PA) and Water Urban Rives (Research, Society and Development, 2021)
Rivers are important determinants of urban morphology, land use and occupation in the territory. Based on a bibliographical and documental review, as well as cartographic information and socioeconomic data analyzed in a geoprocessing tool, the article discusses the roles and functions of urban rivers in the city’s master plans prepared after the 1998 Brazilian Federal Constitution, in Belém-PA, an Amazon metropolis. It shows that, in Belém, the link between urban occupation and watercourses has historically been marked by relationships of conciliation and environmental conflicts. In the 1993 and 2008 Master Plans, it highlights the approaches to urban rivers based on environmental sanitation, housing, mobility and the requalification of the landscape for leisure and tourism purposes. It concludes that the absence of a broad discussion of the morphological, environmental and functional interfaces of urban rivers, results in both broad and segmented guidelines propositions and sectorial actions propositions focused mainly on works, sometimes on basic sanitation, sometimes on waterfront urbanization, sometimes on housing , the vast majority not implemented. Finally, it suggests the need to overcome such barriers, emphasizing the importance of city’s master plans in defining the social function of the city and, therefore, of urban rivers.